'Gemoy' Campaign Strategy: Norman Fairclough's Critical Discourse Analysis - Adam Yogantara; Dewi Kusumaningsih; Muhlis Fajar Wicaksana (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Linguistically, "gemoy" is not listed in the KBBI. This word is a pun on "gemas," which in KBBI means very irritated or very irritated, but in slang, "gemoy" describes more positive feelings of resonance. This article explores how the term 'gemoy' is used strategically in the 2024 presidential election campaign through the lens of Fairclough's critical discourse analysis model. This case study focuses on the @mypresident.id Instagram account and a post entitled "When 'Gemoy' Becomes a Trend in Indonesian Society". This study aims to analyze the use of the term "gemoy" during the 2024 presidential election campaign. This research applies qualitative descriptive methods with critical discourse analysis techniques. The data collected is in the form of all lingual elements, namely words, phrases, clauses, and sentences containing the word "gemoy" in the comment column of netizens on Instagram @mypresident.id. The data were analyzed using the three dimensions of Fairclough's Model Critical Discourse Analysis, which consists of a textual dimension, a discursive dimension, and a sociocultural dimension. The dimensions of sociocultural practices were further analyzed using Dell Hymes' SPEAKING theory. The results show that communication strategies that utilize "gemoy" branding to build politicians' self-image have provided practical examples of how politicians can use digital media to create a more relatable and attractive image in this digital age to influence public opinion. The use of creative and varied language is an important element in politics to attract public attention, build relationships with voters, and achieve political goals, especially for Generation Z and millennials